Hadith #2185 - Sunan Abi Dawud - Bashr bin Hilal al-Swaf بشر بن هلال الصواف; Imran bin Husain; Ja'far bin Sulaiman al-Daba'i جعفر بن سليمان الضبعي; Matraf bin 'Abdullah bin al-Shakhayr مطرف بن عبد الله بن الشخير; Yazid bin Abi Yazid, al-Rashk يزيد بن أبي يزيد الضبعي الرشك (Sunan Abi Dawud)
What do you think if a man divorces his wife while she is menstruating? He said: Abdullah ibn Umar divorced his wife while she was menstruating during the time of the Messenger of Allah (ﷺ).So Umar asked the Messenger of Allah (ﷺ) saying: Abdullah ibn Umar divorced his wife while she was menstruating. Abdullah said: He returned her to me and did not count it (the pronouncement) anything. He said: When she is purified, he may divorce her or keep her with him. Ibn Umar said: The Prophet (ﷺ)
Grade: Sahih

Hadith #3107 - Sunan Abi Dawud - Abdul 'Aziz bin Suhaib عبد العزيز بن صهيب البناني; Abdul Warith bin Sa'id bin Dhakwan عبد الوارث بن سعيد بن ذكوان; Anas ibn Malik; Bashr bin Hilal al-Swaf بشر بن هلال الصواف (Sunan Abi Dawud)
The Prophet (ﷺ) said: When a man comes to visit a sick person, he should say: O Allah, cure Thy servant, who may then wreak havoc on an enemy for your sake, or walk at a funeral for your sake. Abu Dawud said: Ibn As-Sarh (one of the narrators) said: “Ilas-salat (To the Salat)”.
Grade: Sahih